Вокально-хорова робота в процесі підготовки майбутніх вчителів музичного мистецтва в сучасній вищій школі - Гарбуз, Танасій; Потапчук, Тетяна; Harbuz, Tanasii; Potapchuk, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розкриваються питання вокально-хорової роботи в процесі підготовки майбутніх вчителів музичного мистецтва в сучасній вищій школі. Проблеми вибору методів, прийомів та способів навчання, що залежать від студентів, їх інтересів, творчої індивідуальності і досі залишаються недостатньо висвітленими. Це диктує необхідність пошуку нових шляхів і форм роботи зі студентами. З метою формування особистості студента в навчальному процесі сучасна дидактика рекомендує збагатити традиційні методи навчання такими прийомами та способами, які сприяли б формуванню в суб’єкта мотивації учіння, майбутньої професіональної діяльності та змістовних життєвих настанов.The article elaborates on the vocal and choral work in the process of preparation of future teachers of musical art in the modern higher school. The choice of methods, techniques and ways of learning that depend on the students, their interests, creative individuality and still remain insufficiently illuminated. This necessitates the search for new ways and forms of work with students. With the purpose of formation of student's personality in the educational process modern didactics recommends to enrich traditional methods of learning such techniques and methods that facilitate the formation of the subject of learning motivation, future careers and meaningful life attitudes, high activity level, and emotional level of engagement in educational activities, creating conditions for active self-acquisition by students of scientific and professional knowledge, skills and abilities. Mastering the profession of a conductor begins in the classroom individual lessons for mastering the professional knowledge, skills, study choral repertoire. Finally the conductor's skills are formed during all practical activities, while working with the choir. Performing activity conductor requires certain professional psycho-physical and characterological properties. You need to have physical health, needs to be tempered to plastically expressive to convey the character of a musical work during the performance, an important feature of the psychodynamic temperament and character, mastering the skills of analytical and creative thinking.
Оf choral work in the process of preparation of future teachers of musical art in the modern higher school
Keywords: вокально-хорова робота; майбутні вчителі музичного мистецтва; сучасна вища школа; розспівки vocal-choral work; future teachers of musical art; forms; methods; modern high school; warm-ups